1997
DOI: 10.1016/s0014-5793(97)00557-7
|View full text |Cite
|
Sign up to set email alerts
|

A human gene encoding morphine modulating peptides related to NPFF and FMRFamide

Abstract: FMRFaraide-related peptides have been isolated from both invertebrates and vertebrates and exhibit a wide range of biological effects in rats. We show here that in humans 2 FMRFamide-related peptides are encoded by a single gene expressed as a spliced mRNA. The larger predicted peptide (AGEGLNSQFWSLAAPQRFamide) differs from the peptide isolated from bovines (AGEGLSSPFWSLAAPQRFamide) by the substitutions of 2 amino acids. The shorter predicted peptide (NPSF, SQAFLFQPQRFamide) is 3 amino acids longer than the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
110
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(116 citation statements)
references
References 23 publications
(32 reference statements)
3
110
0
Order By: Relevance
“…Up to now, three cDNAs encoding RFRPs have been identified in human (4,5,11,14). In the present study, we have characterized a fourth cDNA encoding a neuropeptide designated 26RFa that exhibits weak structural similarity with the other RFRPs described so far.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Up to now, three cDNAs encoding RFRPs have been identified in human (4,5,11,14). In the present study, we have characterized a fourth cDNA encoding a neuropeptide designated 26RFa that exhibits weak structural similarity with the other RFRPs described so far.…”
Section: Discussionmentioning
confidence: 81%
“…Notably, in human, only three genes encoding RFRPs precursors have been characterized to date. One of these genes encodes the precursor for two RFRPs, i.e., neuropeptide FF (NPFF) and neuropeptide AF (4,5). These two neuropeptides modulate the action of morphine (6) and are thus thought to be involved in the transmission of pain stimuli.…”
mentioning
confidence: 99%
“…by norepinephrine) of energy expenditure in situations that could increase NPAF levels. It has been reported that neuropeptide FF, and possibly NPAF, which is encoded by the same gene precursor (12,13), is secreted in the plasma in a pulsatile manner suggesting that the peptides could act as hormones (15). Under conditions of chronic increase in plasma NPAF, it can be anticipated that modifications of adipocyte catecholamine responsiveness could occur.…”
Section: Absence Of Npaf or Npff Effect On 3t3-l1 Adipocyte Triglycermentioning
confidence: 99%
“…The gene encoding the precursor for these peptides has been recently described in human, rat, mouse, and bovine species (12,13); the two peptides are encoded as a single copy by the same precursor. In the rat, expression of the NPAF and NPFF precursor is limited to discrete regions of the central nervous system including the hypothalamus, medulla, and dorsal horn of the spinal chord (13).…”
mentioning
confidence: 99%
“…Two precursors, proNPFF A and proNPFF B encoding peptides possessing the PQRFamide sequence, have been cloned in mammals [3,4]. The proNPFF A precursor at basic proteolytic sites should generate two PQRFamide containing peptides [3] and the proNPFF B , also called RFamide-related peptides precursor [5], contains a PQRFa sequence and an LPLRFa-containing peptide.…”
mentioning
confidence: 99%